Some Theorems on 3-dimensional Quasi-Sasakian Manifolds - Kalam, Abul (Tamsui Oxford Journal of Mathematical Sciences)
The object of the present paper is to study φ-Ricci symmetric and locally φ-Ricci symmetric 3-dimensional quasi-Sasakian manifolds with structure function β =constant. Also we study η-parallel Ricci tensor and cyclic parallel Ricci tensor with β =constant. Applications of such manifold have been considered. The existence of 3-dimensional φ-Ricci symmetric and locally φ-Ricci symmetric quasi-Sasakian manifolds are also given by concrete examples.